Industry 4 Initiatives in EU - Полозова, Т. В.; Шейко, І. А. (ДУІТ, ХНУРЕ, 2022)
Digitalization of industry is a major component of the digital economy and a determining factor for the growth of the economy as a whole, including the digital industry itself, as a technology producer. Digital technology in many sectors is at the heart of product and manufacturing strategies.
В рамках реалізації проєкту Erasmus+ «Академічна протидія гібридним загрозам» WARN 610133-EPP-1-2019-1-FI-EPPKA2-CBHE-JP
Keywords: Industry 4.0; digitalization; digital technology